MO097BETA BLOCKER PREVENTS CARDIAC MOLECULAR AND MORPHOLOGICAL REMODELLING IN EXPERIMENTAL URAEMIA. (29th May 2021) - Chinnappa, Shanmugakumar; Maqbool, Azhar; Denby, Laura; Mooney, Andrew; Drinkhill, Mark
Abstract: Background and Aims: Fifty years of heart failure research has shown that pathological cardiac remodelling forms a vicious cycle with myocardial dysfunction leading to progressive heart failure (HF) [ Circulation, 102 : IV14-23, 2000]. Fetal gene induction is associated with this process and beta blocker therapy has been shown to prevent it. Although chronic kidney disease (CKD) and HF share similar mediators of cardiac remodelling, the benefits of beta blocker therapy in CKD has not been studied. We, therefore, tested the hypothesis that beta blocker therapy prevents fetal gene induction and pathological cardiac remodelling in experimental uraemia. Method: Wistar rats (n=32) had subtotal nephrectomy (STNx) [ Frontiers in physiology, 10 : 1365, 2019] or sham surgery and were followed up for 10 weeks. The animals were randomly allocated to metoprolol (10mg/kg/day) or vehicle. In vivo and in vitro cardiac assessments were performed, and changes in myocardial fetal gene expression were also studied. Results: Heart rate was significantly lower in metoprolol groups compared to untreated groups demonstrating effective beta blockade (Fig 1A ). Echocardiographic LV mass was significantly higher in untreated STNx group compared to the metoprolol group (896.4 vs 632.2g, P=0.0004). Similar changes were seen with heart weight to tibia ratio (Fig 1B ). There was no significant difference in blood pressure (BP) between treated and untreated STNx animals (123 vs 119 mmHg, P=0.359) (Fig 1A ). STNx increased mRNA expression of fetal genes and there was a trend towards attenuation of this increase with beta blocker therapy (Fig 1C ). Conclusion: Beta blocker therapy ameliorates uraemic pathological cardiac remodelling irrespective of changes to BP. This benefit appears be associated with a reduction of induced fetal gene expression. Further translational research on the benefits of beta blockade in the treatment of uraemic cardiomyopathy is required.